The 24/7 approach to improving outcomes for children affected by chronic trauma and dissociation - Richard Cross (Scottish Journal of Residential Child Care)
Perceptions of childhood have changed over time. In the nineteenth century, for example, children were seen as miniature adults (Aries, 1962). Now they are seen as distinct individuals with an inner world which is very different from the adults who care for them. The same could be said of our understanding of childhood trauma. Over time, various clinicians have theorised about psychological and emotional distress observed in children, but it is only in relatively recent times that they began to attribute some of the causes to early childhood experiences of neglect and trauma. Chronic trauma relates to recurrent exposure to major stressors over time, such as child abuse. Evidence now supports that chronic trauma increases the risk of dissociative disorders (Hart, Nijenius and Steele, 2006). Researchers are now beginning to postulate that dissociation is the key concept to understanding trauma.